2016
DOI: 10.1155/2016/6531948
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Mixed Convection Flow of Chemically Reacting Micropolar Fluid between Porous Parallel Plates with Soret and Dufour Effects

Abstract: The objective of the present study is to investigate the first-order chemical reaction and Soret and Dufour effects on an incompressible MHD combined free and forced convection heat and mass transfer of a micropolar fluid through a porous medium between two parallel plates. Assume that there are a periodic injection and suction at the lower and upper plates. The nonuniform temperature and concentration of the plates are assumed to be varying periodically with time. A suitable similarity transformation is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to u(x,λ,t)=true(U0aV1xhtrue)f/(λ)eiωt, v(x,λ,t)=V1f(λ)eiωt, T(x,λ,t)=true(T1+μV1ρhctrue(ϕ1(λ)+(U0aV1xh)2ϕ2(λ)true)true)eiωt, C(x,λ,t)=true(C1+truenA.hυtrue(g1(λ)+(U0aV1xh)2g2(λ)true)true)eiωt,where λ=y/h, U0‐average velocity at entrance, a=V2/V11, that is, suction/injection ratio, …”
Section: The Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…According to u(x,λ,t)=true(U0aV1xhtrue)f/(λ)eiωt, v(x,λ,t)=V1f(λ)eiωt, T(x,λ,t)=true(T1+μV1ρhctrue(ϕ1(λ)+(U0aV1xh)2ϕ2(λ)true)true)eiωt, C(x,λ,t)=true(C1+truenA.hυtrue(g1(λ)+(U0aV1xh)2g2(λ)true)true)eiωt,where λ=y/h, U0‐average velocity at entrance, a=V2/V11, that is, suction/injection ratio, …”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Therefore, the boundary conditions on the velocity, temperature, and concentration are u=0,v=V1eiωt,T=T1eiωt,C=C1eiωtatλ=0, u=0,v=V2eiωt,T=T2*(x)eiωt,C=C2*(x)eiωtatλ=1,where T2* and C2* are thermal and solutal stratifications at the upper plate given by T2*true(xtrue)=T2+d1x,C2*true(xtrue)=C2+d2x.…”
Section: The Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] obtained numerical solutions for the nonlinear flow and heat transfer of MHD Hartmann–Couette in a Darcian channel with porous medium and Ohmic dissipation. Other interesting and recent research into the thermofluid dynamics of pipes has been reported in [29, 30, 31, 32, 33, 34, 35, 36, 37].…”
Section: Introductionmentioning
confidence: 99%